Deficits in the thalamocortical pathway associated with hypersensitivity to pain in patients with frozen shoulder - Li, Tengshuai; Li, Jie; Zhao, Rui; Zhou, Jiaming; Chu, Xu (Frontiers in Neurology, 2023)
Background and purpose Frozen shoulder (FS) is a chronic pain condition and has been shown to be associated with pain sensitization. However, the underyling brain mechanisms remain unclear. Here, we aimed to explore brain alterations and their association with pain sensitization in patients with FS. Materials and methods A total of 54 FS patients and 52 healthy controls (HCs) were included in this study. Here, we applied both structural and functional magnetic resonance imaging (MRI) techniques to investigate brain abnormalities in FS patients. Voxel-wise comparisons were performed to reveal the differences in the gray matter volume (GMV) and amplitude of low-frequency fluctuation (ALFF) between FS patients and HCs. Furthermore, the region of interest (ROI) to whole-brain functional connectivity (FC) was calculated and compared between groups. Finally, Pearson's correlation coefficients were computed to reveal the association between clinical data and brain alterations. Results Four main findings were observed: (1) FS patients exhibited decreased thalamus GMV, which correlated with pain intensity and pain threshold; (2) relative to HCs, FS patients exhibited a higher level of ALFF within the anterior cingulate cortex (ACC) and the thalamus; (3) FS patients exhibited a significant increase in Tha-S1 FC compared to HCs; and (4) the effect of thalamus GMV on pain intensity was mediated by pain threshold in FS patients. Conclusion The dysfunctional thalamus might induce pain hypersensitivity, which further aggravates the pain in FS patients.